Total and fractionation metal contents obtained with sequential extraction procedures in a sediment core from Terra Nova Bay, West Antarctica - C. E. Casalino; MALANDRINO, Mery; GIACOMINO, AGNESE; ABOLLINO, Ornella (Antarctic Science, 2013)
A suite of 21 elements, namely Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, La, Mg, Mn, Na, Ni, P, Pb, Sr, Ti, V and Zn, was investigated in a sediment core from the Ross Sea, Antarctica. The experimental results were treated by chemometric techniques. The elemental composition of core H2 was found to be mainly dominated by terrigenous elements, but it is also influenced by biological factors, such as the presence of corals. No evidence of anthropogenic contamination was observed, even in the top layer of the sediment. Furthermore, the modified Community Bureau of Reference (BCR) three-step sequential extraction procedure was applied to evaluate metal mobility and availability. The results confirmed the separation between higher and lower sections of the core and showed the presence of Fe as amorphous and crystalline oxide and of Mn mostly as nodules. The high percentages of metals extracted into the fourth fraction indicate their strong binding with the sediment matrix. Finally, BCR procedure was compared to Tessier’s protocol which made it possible to distinguish between mobile and mobilizable fraction. Therefore, in general partitioning procedure must be chosen taking into account the nature of the sample and the aim of the research.